RESULTS OF EDUCATION AT A MARKETING APPROACH - Nabi, Yskak A. (European Scientific Journal, ESJ, 2014)
It is determined that a marketing approach provides for an orientation of managing subsystem when solving any tasks for a consumer. Developed a simplified model of quality management in the quality assurance system of higher education on the basis of EFQM. Revealed reasons and factors leading to move from a qualified approach in the occupational education to competence one. Developed a model of the results of education with a position of competence approach. There has been substantiated a possibility of use of a category "education of a graduate" as measures of achieving the results of education at marketing approach.